Moderate Educational Curriculum and Its Impact on Forming University Student Personality Moderate Psychologically and Socially | المنهج “الوسطي التربوي” وأثره في تكوين شخصية الطالب الجامعي المعتدلة نفسياً ومجتمعياً - Adnan Mustafa (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2015)
The study aimed to indicate the role of moderate approach